Conversation : a History of a declining art - Miller, Stephen (New Haven Yale University Press, 2007)
Ranging from ancient Greece to Enlightenment Britain to contemporary America, this book presents a thorough review of the place conversation has had in culture. Writing in prose that is academic but accessible, Miller (an independent scholar and freelance writer) draws examples from material as diverse as the writings of David Hume and Samuel Johnson to conversations of talk show hosts Ellen DeGeneres and Oprah Winfrey. He identifies a decline in thoughtful conversation due to electronic media--"conversation avoidance devices" such as iPods, instant messaging, and e-mail--but he seems to suggest that the anger in the current political climate and the lack of raillery (i.e., good-humored disagreement) are much more destructive to the art of conversation than are electronic devices. Miller's concluding chapters offer some hope for the art of conversation, as he calls his readers to embrace politeness and listening as ways to facilitate conversation, as opposed to the "authenticity" of speaking one's mind that plagues current culture. A thorough history of a declining art and a persuasive argument for the reviving of that lost art in contemporary America, this book is a delightful read. ^BSumming Up: Essential. All readers; all levels. R. McManus Marietta College
Keywords: Comunicación oral -- Historia; Análisis del discurso